Volume 1D, Symposia: Transport Phenomena in Mixing; Turbulent Flows; Urban Fluid Mechanics; Fluid Dynamic Behavior of Complex P 2014
DOI: 10.1115/fedsm2014-21377
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Dynamic Power Line Rating Concept for Improved Wind Energy Integration Over Complex Terrain

Abstract: Dynamic Line Rating (DLR) is a smart grid technology that allows the rating of power line conductor to be based on its real-time temperature. Currently, conductors are generally given a conservative static rating based on near worst case weather conditions. Using historical weather data collected over a test bed area in Idaho, we demonstrate there is often additional transmission capacity not being utilized under the current static rating practice. We investigate a DLR method that employs computational fluid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In Canada, it analyzed the DLR system for a wind installation and showed an average 22% capacity increase over SLR 76% of the time [20]. According to case studies in the United Kingdom (UK), DLR integration on all major circuits in England and Wales resulted in a capacity increase of up to 30% [18], [21]. Another study reported that the DLR system in Ireland increased by 0.2 PU rating between 75% and 95% of the time for individual lines [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Canada, it analyzed the DLR system for a wind installation and showed an average 22% capacity increase over SLR 76% of the time [20]. According to case studies in the United Kingdom (UK), DLR integration on all major circuits in England and Wales resulted in a capacity increase of up to 30% [18], [21]. Another study reported that the DLR system in Ireland increased by 0.2 PU rating between 75% and 95% of the time for individual lines [22].…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that the DLR system in Ireland increased by 0.2 PU rating between 75% and 95% of the time for individual lines [22]. Based on the international experience in Europe, DLR provides capacity increment between 5% to 70% higher than SLR depending on location, due to different weather conditions [21], [23]. It is worth noting that weather conditions in Southeast Asia differ significantly from those in western nations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies into DLR have shown potential for day ahead planning [8], or as a way for easing congestion of lines [9,10]. Natural synergy with increased wind power generation coupled with thermal cooling also provides large benefits to promote integration with DLR technology [11][12][13][14] Results of analyzing collected weather data in the field has shown potential to increase ampacity above static for for case studies in Canada [15,16], the US and the UK [17] and forecasted weather data in Ireland [18].…”
Section: Introductionmentioning
confidence: 99%